2022
DOI: 10.1016/j.xcrm.2021.100487
|View full text |Cite
|
Sign up to set email alerts
|

Immunological factors, but not clinical features, predict visceral leishmaniasis relapse in patients co-infected with HIV

Abstract: Highlights d Visceral leishmaniasis patients co-infected with HIV suffer from frequent VL relapse d VL relapse is associated with low CD4 + T cell counts and low production of IFN-g d VL relapse is associated with increased PD1 expression on CD4 + and CD8 + T cells d These three markers can predict whether and when these patients relapse

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(90 citation statements)
references
References 60 publications
6
82
1
1
Order By: Relevance
“…We have recently shown that throughout follow-up, as compared to VL patients, VL/HIV patients display (12): - higher parasite load; - impaired antigen-specific IFNγ production by whole blood cells; - lower CD4 + T cell counts; - higher PD1 expression on CD4 + and CD8 + T cells. Our data also show that 78.1% of VL/HIV patients experience at least one relapse (12). Reliable data on both clinical and immunological parameters from VL/HIV patients who experience VL relapse are still limited: the following markers have been shown to predict VL relapse in VL/HIV patients: - failure to clear parasite load after anti-leishmanial treatment (20), as well as presence of circulating Leishmania DNA (22); - low CD4 + T cell counts (5, 20); - previous VL episodes in VL/HIV patients (5, 20, 23), though a study showed no association between a previous history of relapse and increased risks of future relapse (24).…”
Section: Introductionsupporting
confidence: 64%
See 4 more Smart Citations
“…We have recently shown that throughout follow-up, as compared to VL patients, VL/HIV patients display (12): - higher parasite load; - impaired antigen-specific IFNγ production by whole blood cells; - lower CD4 + T cell counts; - higher PD1 expression on CD4 + and CD8 + T cells. Our data also show that 78.1% of VL/HIV patients experience at least one relapse (12). Reliable data on both clinical and immunological parameters from VL/HIV patients who experience VL relapse are still limited: the following markers have been shown to predict VL relapse in VL/HIV patients: - failure to clear parasite load after anti-leishmanial treatment (20), as well as presence of circulating Leishmania DNA (22); - low CD4 + T cell counts (5, 20); - previous VL episodes in VL/HIV patients (5, 20, 23), though a study showed no association between a previous history of relapse and increased risks of future relapse (24).…”
Section: Introductionsupporting
confidence: 64%
“…For this cross-sectional study, we followed the cohort of 49 VL/HIV patients (median age 33.5±1.0 years) that was described in (12). Twenty-one patients presented with their first episode of VL (primary VL/HIV, P VL/HIV) and 28 with at least one previous episode of VL (recurrent VL/HIV, R VL/HIV, Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations